2021
DOI: 10.1177/15330338211004924
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Nomogram for Individually Predicting of Vascular Invasion in Gastric Cancer

Abstract: Purpose: Vascular invasion (VI) is associated with recurrence and is an indicator of poor prognosis in gastric cancer (GC). Pre-operative identification of VI may guide the selection of the optimal surgical approach and assess the requirement for neoadjuvant therapy. Methods: A total of 271 patients were retrospectively collected and randomly allocated into the training and validation datasets. The least absolute shrinkage and selection operator regression model was used to select potentially relevant features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…Meng Y et al. ( 12 ) proposed a nomogram consisted of clinical indicators with AUC of 0.774 in the testing datasets. Chen X et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meng Y et al. ( 12 ) proposed a nomogram consisted of clinical indicators with AUC of 0.774 in the testing datasets. Chen X et al.…”
Section: Discussionmentioning
confidence: 99%
“…Meng Y et al. ( 12 ) have developed a nomogram based on pre-operative features to predict LVI, but without involving quantitative indicators on enhanced CT. Ma Z et al. ( 13 ) found correlation of LVI with CT attenuation values on multiphasic enhanced CT, but without external validation of the results.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, the Lauren classi cation and quantitative features were incorporated into the models to assist with predicting the LVI status for the rst time. Previous studies [14,[30][31][32][33] have shown that Lauren classi cation and LVI status are independent factors affecting the e cacy of and prognosis after chemotherapy, indicating that our research has important signi cance in the treatment and prognosis of GC.…”
Section: Discussionmentioning
confidence: 65%
“…Studies based on texture analysis of CT images have shown that CT radiomics features combined with clinicopathological factors such as T stage, N stage, and American Joint Committee on Cancer (AJCC) stage can be used to establish predictive models that can evaluate LVI status preoperatively [7]. Some studies used clinicopathological factors in combination with nomograms to predict vascular invasion in GC; however, these studies did not incorporate Lauren classi cation into their models as predictive factor, nor did they obtain quantitative information from CT images, such as the contrast enhancement rate [14]. Therefore, we established radiomics models based on CECT images to evaluate LVI status before surgery and proposed two hypotheses.…”
Section: Introductionmentioning
confidence: 99%
“…Microvascular invasion (MVI) is an early pathological manifestation of LN and other organ metastasis in malignant tumors. It involves the invasion of tumor cells or tumor thrombus into the blood vessels and/or lymphatic walls near the tumor, playing a key role in tumor cell proliferation and metastasis [5,6,7].…”
Section: Introductionmentioning
confidence: 99%